AN ANALYSIS OF ENGLISH LANGUAGE ACQUISITION AS A FOREIGN LANGUAGE ON VENDORS IN MANDALIKA BEACH LOMBOK - Jumadil, Jumadil; Siswana, Siswana (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
Language acquisition is a human process in acquiring the ability to understand the management of words for communication purposes. The pre-requisite abilities in language acquisition include syntax, phonetics, and a large vocabulary. Language acquisition is a field of macro linguistic study that combines education and linguistics while learning refers to formal situations. A foreign language is a language that is always learned in a context where member societies are not accustomed to using it. The acquisition of a foreign language is usually influenced by the individual’s interest and/or plans for the future to utilize the acquired language and this foreign language is acquired after the first language to some degree. This study examines how vendors acquire English-speaking competence and the barriers they face. The researchers used a qualitative research design with naturalistic inquiry in this study. The results found that both vendors acquired English as a foreign language proficiency by using diction, syntax, and phonetics. At the same time, some of the obstacles faced were difficulties in pronunciation, phonological speech, morphological and syntactic levels, and at the semantic level in compiling English sentences. All the obstacles faced by traders due to the influence of their mother tongue. The implications of the findings are discussed regarding teaching English as a foreign or second language among adult learners, both formal and non-formal tourism workers. Expected to pay more attention to how to pronounce and compose correct English sentences correctly